A phase 1 dosing study of ruxolitinib in children with relapsed or refractory solid tumors, leukemias, or myeloproliferative neoplasms: A Children's Oncology Group phase 1 consortium study (ADVL1011). Issue 10 (13th May 2015) - Loh, Mignon L.; Tasian, Sarah K.; Rabin, Karen R.; Brown, Patrick; Magoon, Daniel; Reid, Joel M.; Chen, Xuejun; Ahern, Charlotte H.; Weigel, Brenda J.; Blaney, Susan M.
<x xml:space="preserve">Abstract</x> Background Ruxolitinib, an orally bioavailable JAK1/JAK2 inhibitor, may treat cancers with CRLF2 and/or JAK pathway mutations. Procedure A phase 1 trial of ruxolitinib was performed to determine the maximum tolerated or recommended phase 2 dose, dose‐limiting toxicities (DLTs), pharmacokinetics (PK), and pharmacodynamics (PD) in children with recurrent/refractory solid tumors (STs). Ruxolitinib was administered twice daily (BID) in 28‐day cycles at five dose levels (15, 21, 29, 39, and 50 mg/m2/dose). PK and PD studies were performed during cycle 1. Toxicity, preliminary efficacy, and PK/PD were also assessed in children with relapsed/refractory hematologic malignancies (HMs). Results Forty‐nine patients were enrolled, 28 with STs (dose escalation cohort) and 21 with HMs. Ruxolitinib was well‐tolerated with one DLT per cohort of six patients at dose levels (DLs) 2–5. One patient with an ST had grade 5 multi‐organ failure at DL2. One patient each at DL3 and DL4 had a grade 4 neutropenia, and one patient at DL5 had a grade 4 creatinine phosphokinase elevation. No objective responses were observed in patients with STs. One patient with polycythemia vera achieved a partial response and received 18 cycles of ruxolitinib. The PK of ruxolitinib were similar to that in adults. Partial inhibition of phosphorylated JAK2, STAT5, and S6 was observed in in vitro plasma inhibitory activity PD assay. Conclusion Ruxolitinib was well tolerated in children with refractory cancer. The recommended phase 2 dose for continuous BID oral administration is 50 mg/m2/dose. Subsequent evaluation of ruxolitinib in combination with cytotoxic chemotherapy in children, adolescents, and young adults with JAK‐mutant leukemias is planned. Pediatr Blood Cancer 2015;62:1717–1724. © 2015 Wiley Periodicals, Inc.